Antioxidant Activity Interaction of Rosella (Hibiscus sabdariffa L.) and Soursop Leaves (Annona muricata L.) Brew Combination Using the FRAP (Ferric Reducing Antioxidant Power) Method - Apriyani, Zupita; Perwitasari, Melania; Beandrade, Maya Uzia; Nathalia, Dede Dwi (Journal of Fundamental and Applied Pharmaceutical Science, 2026)
Free radical compounds can damage human body cells, triggering degenerative diseases. The prevention effort is to consume natural ingredients such as rosella and soursop leaves, which have the potential as antioxidants. This study is to determine the antioxidant activity of rosella and soursop leaf brew and their combination interaction. This research uses experimental quantitative methods. The samples used were F1 (rosella), F2 (soursop leaves) and their combination with concentration variations F3 (50:50), F4 (75:25), and F5 (25:75). Antioxidant activity values were determined by the FRAP method and analyzed using One-way ANOVA. The antioxidant activity value of rosella, soursop leaves and their combinations F3, F4 and F5 are 69.222 µg/mL; 133.701 µg/mL; 104.049 µg/mL; 57.382 µg/mL; and 115.438 µg/mL. Analysis: One-way ANOVA test of rosella and soursop leaf brew with several concentration variations has significant differences, sig. 0.000 <0.05 on the value of antioxidant activity. The antioxidant activity of the soursop leaf brew was higher than rosella brew. The combination interaction was categorized as antagonistic, with a % difference <0.